2019
DOI: 10.1088/1757-899x/527/1/012051
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different rejuvenating agents on the mechanical performance of recycled bituminous mixture

Abstract: Reclaimed asphalt pavement (RAP) is a waste material generated from pavement milling activity. Rejuvenating agent is introduced to restore the properties of aging bitumen in RAP. Many studies have been investigated the performance of recycled mixture incorporating RAP with oil-based (OB) rejuvenating agent, but there is still limited research on water-based (WB) rejuvenating agent. Therefore, this study evaluated the performance of mixture incorporating RAP with OB and WB rejuvenating agents (RAP-OB and RAP-WB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The higher ITS values indicate the higher stiffness and higher viscosity of the RAP asphalt binders. This result is similar to those obtained by Idham et al [ 51 ], who concluded that the RAP has a significant impact on the ITS, where higher RAP contents produced higher ITS values.…”
Section: Resultssupporting
confidence: 91%
“…The higher ITS values indicate the higher stiffness and higher viscosity of the RAP asphalt binders. This result is similar to those obtained by Idham et al [ 51 ], who concluded that the RAP has a significant impact on the ITS, where higher RAP contents produced higher ITS values.…”
Section: Resultssupporting
confidence: 91%